Changes in the Antenatal Utilization of High-Risk Obstetric Services and Stillbirth Rate during the COVID-19 Pandemic - Oakes, Megan C.; Zhang, Fan; Stevenson, Lori; Porcelli, Bree; Carter, Ebony B.; Raghuraman, Nandini; Kelly, Jeannie C. (American Journal of Perinatology, 2021)
Objective The primary objective of this study was to evaluate coronavirus 2019 (COVID-19) pandemic–related changes in the antenatal utilization of high-risk obstetric services. Our secondary objective was to characterize change in stillbirth rate during the pandemic.Study Design This is a retrospective, observational study performed at a single, tertiary care center. Maternal-Fetal Medicine (MFM) visits, ultrasounds, and antenatal tests of fetal well-being during the pandemic epoch (2020), which spans the first 12 weeks of the year to include pandemic onset and implementation of mitigation efforts, were compared with the same epoch of the three preceding years visually and using general linear models to account for week and year effect. An analysis of stillbirth rate comparing the pandemic time period to prepandemic was also performed.Results While there were decreased MFM visits and antenatal tests of fetal well-being during the pandemic epoch compared with prepandemic epochs, only the decrease in MFM visits by year was statistically significant (p < 0.001). The stillbirth rate during the pandemic epoch was not significantly different when compared with the prepandemic period and accounting for both week (p = 0.286) and year (p = 0.643) effect.Conclusion The COVID-19 pandemic resulted in a significant decrease in MFM visits, whereas obstetric ultrasounds and antenatal tests of fetal well-being remained unchanged. While we observed no change in the stillbirth rate compared with the prepandemic epoch, our study design and sample size preclude us from making assumptions of association. Our findings may support future work investigating how changes in prenatal care for high-risk obstetric patients influence perinatal outcomes.Key Points
Keywords: COVID-19; SARS-CoV-2; SARS; coronavirus; high-risk pregnancy; maternal-fetal medicine; antenatal; ultrasound